Choosing China: Unpacking the motivations of international students through a case study in Shanghai - Zhang, Yu; Qin, Tian; Zhang, Xiaoqiao (Journal of International Students, 2026)
The internationalization of higher education continues to accelerate with globalization, making China one of the top host nations for international students. This qualitative case study took place at a university in Shanghai, with 76 international students from 20 countries enrolled in the same English-taught engineering program. This research explored the motivations of international undergraduate students pursuing degree programs and their overall experience in China. The research reveals four main factors that shape students’ decision-making: academic reputation, social network influence, affordability, and safety. Additionally, many students identified academic difficulties even as they acknowledged the benefits of studying in China. This study recommends that Chinese universities improve their recruitment tactics, including expanding communication channels, increasing school visits, and strengthening alumni networks to attract more qualified and well-suited students and enhance their reputation.